Using mixed methods to understand sensitive wildlife poisoning behaviours in northern Cambodia - de Lange, E; Milner-Gulland, EJ; Yim, V; Leng, C; Phann, S; Keane, A (Cambridge University Press, 2020)
In northern Cambodia, threatened wildlife, livestock and people are being poisoned by pesticides deposited in seasonal waterholes. Addressing this critical conservation threat requires understanding the drivers of poisoning behaviours and the social contexts in which they occur. This study across 10 communities in two protected areas aimed to provide a first assessment of this phenomenon. We used the theory of planned behaviour to measure socio-psychological determinants of behaviour and deepened this understanding using informant interviews and focus group discussions. Informants reported that so-called termite poisons, including powerful carbamates, are deliberately deposited at waterholes to catch wildlife for consumption. This method is perceived to be low effort and high efficacy, and perceptions of the health risks vary. Predominant users are young men and children, but it is unclear whether the practice is related to food insecurity. Threatened wildlife species reported as affected include the giant ibis Pseudibis gigantea and vulture species. Overall, social norms are strongly negative towards poisoning; 75% of survey respondents perceived negative norms because of impacts on human and livestock health, environmental quality, and risks of legal sanctions. This has led to interventions by local authorities in half of the studied villages. We suggest that future interventions should raise the salience of negative norms by providing a non-conflictual mechanism for community members to participate in monitoring and sanctioning, such as a reporting hotline. Regulatory interventions are also required to control the supply of restricted pesticides.